Legal Protection of Victims of Fake And Lie News (Hoax) in The Electronic Transaction Information Law - Hakni Kusuma Muahammad Reyhan Arkan; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2023)
Today the pace of information development that no longer recognizes barriers and boundaries, as a result of globalization and technological advances deserves more attention from a legal perspective. Technological progress has a myriad of benefits but also has various challenges that must be faced, in this case the rapid spread of information through social media whose validity or truth cannot be easily determined. Evidence of the negative impact of technological progress can be seen in the many cases caused by the misuse of technology to commit fraud, especially in spreading hoaxes and electronic transactions, so that in this study the focus is on being able to see a legal perspective in protecting victims of fake news and lie (hoaxes). This research was analyzed using normative juridical and qualitative descriptive methods. This study aims to confirm that the basic regulations for the spread of fake or fake news (hoaxes) have been regulated in Law No. 19 of 2016 precisely in article 28 paragraph (1) and article 27 paragraph (3), besides that the author through this research wants to focus on legal protection for victims of fake and fake news (hoaxes) that are in effect at this time, the article besides these rules there are other regulations relating to the spread of fake and fake news (hoaxes), namely article 14 and article 15 of Law No. 1 of 1946, as well as article 311 and article 378 of the Criminal Code. This research will produce answers regarding legal protection that can be sought by victims of spreading fake news and lies (hoax).